Reclaiming development studies: essays for Ashwani Saith. - Arsel, Murat (Anthem frontiers of global political economy, 2021)
As the mission, relevance and intellectual orientation of development studies is increasingly being challenged, this collection of essays argues for the continued necessity to ground the field in a critical political economy approach informed by the contributions of Ashwani Saith.